2014
DOI: 10.1111/jjns.12049
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer knowledge and sun protection behavior among nursing students

Abstract: This study revealed that the knowledge levels and protective behavior of first year nursing students against the harmful effects of the sun and for protection against skin cancer were alarmingly low. It also showed that the knowledge levels of the fourth year nursing students were average, but that their protective behavior was very insufficient. These findings suggest that it is of extreme importance to acquire knowledge and behavior for protection against skin cancers in the education of nursing students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 15 publications
0
34
0
7
Order By: Relevance
“…Most medical professionals perceived their skin cancer risk as average and thought that morning and late afternoon were good times for outdoor activities in autumn, spring and summer . Abu‐Abed et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most medical professionals perceived their skin cancer risk as average and thought that morning and late afternoon were good times for outdoor activities in autumn, spring and summer . Abu‐Abed et al .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight per cent to 86% of different medical professionals applied sunscreen during sun exposure . Sixty‐one per cent of Turkish nurses reported that when buying sunscreen, the SPF of the sunscreen was their top consideration …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the efficiency of these programs has not been evaluated for the last 10 years, there is a strong need to plan experimental studies and prospective cohort studies on these programs. The sample of the school-based studies on sun protection in Turkish society consisted of university students [39][40][41][42][43][44][45][46] , high school students 47,48 , secondary school students [49][50][51][52] , primary and secondary school students 53 , and primary school students 54 . High school students were included along with their teachers 48 in one of these studies, while primary school students were included along with their parents 54 in another study.…”
Section: Discussionmentioning
confidence: 99%